Respostas

  • Usuário do Brainly
2013-06-06T16:34:38-03:00

Observe que:

 

\text{a}_2-\text{a}_1=\text{r}

 

Desta maneira, podemos afirmar que:

 

\text{a}_6-\text{a}_1=5\text{r}

 

Desta maneira:

 

\text{a}_6-\text{a}_1=5\text{r}=57-2

 

Logo:

 

5\text{r}=57-2

 

E, portanto:

 

\text{r}=\dfrac{55}{5}=11

1 1 1
2013-06-06T16:41:02-03:00

an:57                                                        

a1:2                                                           

n:6                                                               

r: ?                                                  

an = a1 + (n-1) x r

57= 2 + (6-1) x r

57= 2 + 6r - r

57= 2 + 5r 

5r = 2 - 57

5r = 55

r = 55/5

r = 11